Changing Epidemiology of Invasive Fungal Disease in Allogeneic Hematopoietic Stem Cell Transplantation - Pedro Puerta-Alcalde; Carolina Garcia-Vidal (Journal of Fungi, 2021)
Invasive fungal disease (IFD) is a common cause of morbidity and mortality in patients with hematologic malignancies, especially among those undergoing allogeneic hematopoietic stem cell transplantation (HSCT). The epidemiology of IFD in HSCT patients has been evolving over the last decades, mainly in relation to changes in HSCT therapies such as antifungal prophylaxis. A progressive decrease in Candida albicans infection has been documented, alongside a progressive increase in infections caused by non-albicans Candida species, filamentous fungi, and/or multidrug-resistant fungi. Currently, the most frequent IFD is invasive aspergillosis. In some parts of the world, especially in north Central Europe, a high percentage of Aspergillus fumigatus isolates are azole-resistant. New diagnostic techniques have documented the existence of cryptic Aspergillus species with specific characteristics. An increase in mucormycosis and fusariosis diagnoses, as well as diagnoses of other rare fungi, have also been described. IFD epidemiology is likely to continue changing further due to both an increased use of mold-active antifungals and a lengthened survival of patients with HSCT that may result in hosts with weaker immune systems. Improvements in microbiology laboratories and the widespread use of molecular diagnostic tools will facilitate more precise descriptions of current IFD epidemiology. Additionally, rising resistance to antifungal drugs poses a major threat. In this scenario, knowledge of current epidemiology and accurate IFD diagnoses are mandatory in order to establish correct prophylaxis guidelines and appropriate early treatments.